Increasing plant diversity enhances soil organic carbon storage in typical wetlands of northern China - Liu, Hua-Bing; Yang, Li-Ping; Gao, Jun-Qin; Li, Qian-Wei; Li, Xing-Li; Feng, Jiu-Ge; Yu, Fei-Hai (Frontiers in Plant Science, 2024)
Soil organic carbon plays an important role in climate change mitigation, and can be strongly affected by plant diversity. Although a positive effect of plant diversity on soil organic carbon storage has been confirmed in grasslands and forests, it remains unclear whether this effect exists in wetlands. In this study, we investigated plant diversity, soil properties and soil organic carbon across five typical wetlands of northern China, to test the effect of plant diversity on soil organic carbon and clarified the regulators. Increasing plant diversity significantly increased belowground biomass of wetland plant communities, and both soil organic carbon content and storage were significantly positively related to wetland plant diversity. The positive effect of plant diversity was influenced by belowground biomass of wetland plant communities, soil microbial biomass carbon, and soil properties, especially soil water content and bulk density. The structural equation model showed that soil organic carbon storage was dominantly affected by microbial biomass carbon, plant diversity and biomass, with standardized total effects of 0.66 and 0.47, respectively, and there was a significant positive relationship between soil organic carbon and microbial biomass carbon. These results suggest that increasing plant diversity can potentially promote the ability of wetlands to store organic carbon in soils. The findings highlight the importance of plant diversity on soil organic carbon in wetland ecosystems, and have implications for managing wetlands to increase carbon sinks and to mitigate global climate change.